Description of the Adult Male of Stylops advarians Pierce (Strepsiptera: Stylopidae) - Balzer, Zachary S.; Davis, Arthur R. (Zootaxa, 2019)
The morphology of the adult male of Stylops advarians Pierce is described for the first time. This species was previously known only from the endoparasitic adult female and the host-seeking, first-instar larva. Members of Stylops are cosmopolitan, and Stylops advarians can be found parasitizing Andrena milwaukeensis Graenicher in western Canada.